Balanced Nutrition Menu Education During Fasting to Support the Learning Process of Islamic Boarding School Students - Salamy, Nanda Fadhilah Witris; Kombih, Muhammad Fifin; Setiarsih, Dini; Mubarak, Achmad Yarziq; Matin, Nur Sophia (Indonesia Berdaya, 2026)
The nutritional intake of students in Islamic boarding schools during Ramadan is often dominated by carbohydrates, with limited attention to balanced macro- and micronutrient consumption. This imbalance may affect health and learning concentration. This community engagement program aimed to enhance students’ understanding of balanced nutrition during fasting based on physiological principles. The activity was conducted at Pondok Pesantren Assalafi Al Fithrah Surabaya through three phases: initial survey, interactive educational sessions, and follow-up evaluation. Thirty-one students participated in both pretest and posttest assessments. The results showed an increase in the average knowledge score from 54.19 to 66.77 (p = 0.005), indicating a statistically significant improvement. The participatory educational approach proved effective in enhancing students’ nutritional literacy. The program suggests that physiology-based nutrition education can serve as a strategic approach to improving health awareness in Islamic boarding schools. Integrating nutrition education into institutional food management policies is recommended to promote sustainable healthy eating habits.